2019
DOI: 10.21608/asejaiqjsae.2019.31622
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Study on Jerusalem Artichoke Plants (Helianthus Tuberosus L.) Under Two Types of Soils

Abstract: Two field experiments were carried out on Jerusalem artichoke crop during two successive seasons of 2016 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Sawicka (2002), found that the inulin content was highest when fertilizing with nitrogen 50 kg ha -1 . In contrary, Nashwa et al (2019) showed that the application of 100 kg ha -1 N led to an increase in the percentage of inulin in the tubers, but our results showed highest content of inulin at relatively low nitrogen application rate at both plants densities analysed in the experiment. As the nitrogen applied increased twice or triple the results regarding the inulin content were relatively similar, respectively 13.1% (A2B1) and 13.06% (A3B2).…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…Sawicka (2002), found that the inulin content was highest when fertilizing with nitrogen 50 kg ha -1 . In contrary, Nashwa et al (2019) showed that the application of 100 kg ha -1 N led to an increase in the percentage of inulin in the tubers, but our results showed highest content of inulin at relatively low nitrogen application rate at both plants densities analysed in the experiment. As the nitrogen applied increased twice or triple the results regarding the inulin content were relatively similar, respectively 13.1% (A2B1) and 13.06% (A3B2).…”
Section: Resultscontrasting
confidence: 94%
“…The dry weight of JA tubers and the rate of inulin increased with the increase of the nitrogen rate up to 90 kg ha -1 N (Ezzat et al, 2013). Sawicka (2002), found that the inulin content was highest when fertilizing with 50 kg ha -1 N, while the dry matter content of the tubers increased to 100 kg ha -1 N. Also, Nashwa et al (2019) showed that the application of 100 kg ha -1 N led to an increase in the percentage of dry matter and inulin in the tubers. Tony (2013) showed that the use of mixed bio-fertilizers with chemical fertilization led to an increase in dry weight by 18.1% compared to the unfertilized control.…”
Section: Resultsmentioning
confidence: 99%